2021
DOI: 10.5888/pcd18.200490
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Involvement in Addressing Public Health Priorities and Community Needs: The Allegheny County Racial and Ethnic Approaches to Community Health (REACH) Project

Abstract: Community–clinical linkages are connections between community and clinical sectors to improve population health, and community-based pharmacists are well positioned to implement this strategy. We implemented a novel approach to community–clinical linkages in African American communities in which community-based pharmacists implement screenings for chronic disease and social determinants of health, make referrals to clinical and social services, and follow up with patients to support linkage to care in nontradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Figure 2 includes the context or setting for the included sources. Primary health care (n=58) was the setting for almost half of the included sources, 21 , 37 , 39 42 , 44 , 45 , 47 51 , 54 , 56 , 57 , 62 , 63 , 65 , 67 , 72 , 73 , 75 , 77 , 79 , 81 84 , 87 , 88 , 91 , 94 96 , 98 100 , 104 , 106 , 108 110 , 112 , 114 116 , 122 , 123 , 125 , 128 , 129 , 140 , 142 , 143 , 146 , 152 , 153 followed by health service/delivery system (n=31), 35 , 36 , 38 , 43 , 71 , 92 , 93 , 97 , 102 , 103 , 105 , 107 , 111 , 117 121 , 124 , 126 , 130 , 132 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 includes the context or setting for the included sources. Primary health care (n=58) was the setting for almost half of the included sources, 21 , 37 , 39 42 , 44 , 45 , 47 51 , 54 , 56 , 57 , 62 , 63 , 65 , 67 , 72 , 73 , 75 , 77 , 79 , 81 84 , 87 , 88 , 91 , 94 96 , 98 100 , 104 , 106 , 108 110 , 112 , 114 116 , 122 , 123 , 125 , 128 , 129 , 140 , 142 , 143 , 146 , 152 , 153 followed by health service/delivery system (n=31), 35 , 36 , 38 , 43 , 71 , 92 , 93 , 97 , 102 , 103 , 105 , 107 , 111 , 117 121 , 124 , 126 , 130 , 132 ,…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we found that indicators for measuring health equity in our included sources were not well described or, in some cases, not reported (n=68). 21 , 36 , 37 , 40 , 47 , 50 , 51 , 53 55 , 57 , 59 , 60 , 66 , 68 , 69 , 71 , 74 , 76 , 78 , 79 , 81 , 82 , 88 , 90 92 , 94 , 95 , 98 , 100 , 102 , 103 , 106 108 , 110 , 111 , 113 116 , 118 121 , 123 126 , 129 – 135 , 139 , 143 146 , 148 , 149 , 151 , 153 , 154 When indicators were included (n=54), sources revealed a considerable array of indicators that were employed to measure health equity integration. 35 , 38 , 39 , 41 46 , 48 , 49 , 52 , 56 , 58 , 61 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DUCIH's Community Health Initiatives arm includes interdisciplinary school-based asthma clinics, a pharmacist-led community-clinical linkages program including chronic disease and social determinants of health screenings and care coordination, community-based chronic disease prevention programs (smoking cessation, CDC's Diabetes Prevention Program, etc. ), and community-based vaccine clinics (Elliott et al, 2021). Through these programs, strong partnerships have been built over time with the Allegheny County Health Department (ACHD), school districts, churches, federally qualified health centers (FQHCs), the Housing Authority of the City of Pittsburgh, and community-based organizations, among others.…”
Section: Duquesne University Center For Integrative Healthmentioning
confidence: 99%
“…Before the pandemic, various schools at the university partnered with ACHD on projects related to Head Start, screening, vaccination, and health education. This includes a five-year project, The Allegheny County Racial and Ethnic Approaches to Community Health (REACH) Project, to implement screenings for chronic disease and social determinants of health using communitybased pharmacists (Elliott et al, 2021).…”
Section: Duquesne University Center For Integrative Healthmentioning
confidence: 99%